Education of Leading Pedagogical Staff in Partial Leadership Competencies - Opletalová, Alena; Nováková, Zdenka (Civilia, 2021)
The paper focuses on the area of further education of pedagogical staff. Specifically, it deals with a group of leading pedagogical staff, respectively leaders of schools and school facilities. At present, courses and other educational activities are offered in the field of further education, which, however, often do not reflect current trends in the management of kindergartens, small schools, primary schools, secondary schools, youth homes and institutions for institutional and protective education and institutions providing hobby education. The presented contribution responds to this need in the field of further education. Based on the suggestions of leading pedagogical staff, various interest groups and also the Ministry of Education, Youth and Sports, there was a need to prepare and offer a quality educational program aimed at increasing the managerial competencies of leading pedagogical staff.The aim of the presented paper is to theoretically define the issue of further education of leading pedagogical staff in the Czech Republic on the basis of an analysis of the educational needs of this target group to present a proposal for a new educational program. The educational program contains a basic thematic block focused on the area of pedagogical leadership of school principals and school facilities. Another part of the educational program consists of 6 sub-thematic blocks, which are selective and aimed at increasing managerial competencies for leading pedagogical staff of kindergartens, small schools, primary schools, secondary schools, youth homes and institutions for institutional and protective education and staff education in various sub-areas of their operation. Through a questionnaire survey and brainstorming, data from the analysis were obtained and further evaluated in the form of specific educational proposals. A new educational project aimed at increasing the competencies of pedagogical staff was also verified through full-time and distance forms of implemented seminars and also by sharing experiences from this education. So far, 70 leading pedagogical staff have participated in the verification.The proposed new educational program will then be in accordance with the provisions of the Decree of the Ministry of Youth, Education and Sports No. 317/2005 Coll., on further education of teachers, accreditation commission and career system of teachers, as amended and Act No. 563/2004 Sb., on pedagogical staff and on the amendment of certain acts, as amended, submitted as a study program to meet other qualification requirements for assessment of accreditation.
Keywords: Further education of pedagogical staff; Leading pedagogical staff; Educational program